How Positive Psychology Fosters Employee Adaptability Through Resilience and Job Satisfaction among Banking Employees - Elkunny Dovir Siratan; Tju Meriana; Vania Priskila; Sherly Sherly; Novia Sri Parindu Purba (International Journal of Psychology and Health Science, 2026)
Digital transformation, regulatory change, and competitive pressure require banking employees to possess a high level of adaptability in order to remain effective in a dynamic work environment. This study aims to examine the effect of positive psychological capital on employee adaptability, with job resilience and job satisfaction serving as mediating variables among employees of international and multinational banks in Indonesia. A quantitative approach was employed using purposive sampling, involving 160 permanent employees working in operational, customer service, and frontline divisions with a minimum tenure of two years. Data were collected through a five point likert scale questionnaire and analyzed using SmartPLS. The findings indicate that all constructs meet the criteria for validity and reliability, and that the proposed model demonstrates adequate explanatory power. Positive psychological capital has a positive and significant effect on employee adaptability, job resilience, and job satisfaction. In addition, job resilience and job satisfaction positively influence employee adaptability and significantly mediate the relationship between positive psychological capital and employee adaptability. This study concludes that employee adaptability in the banking sector is shaped not only by job demands, but also by internal psychological resources that foster resilience and job satisfaction in responding to organizational change.